ISLAMIC RELIGIOSITY GUIDANCE APPROACHES ON MENTAL HEALTH DISORDER - Awang Saputra; Adi Fahrudin; Munaya Fauziah; Saiful Bahri; Muhammad Fachri (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
The productive age population in Indonesia in 2022 will reach 69%, with great potential for increasing economic growth. However, there is an increasing threat of mental disorders, which results in low productivity and hinders economic growth. Mental health disorders have psychologically weak conditions that need strengthening through religious guidance. Muslims believe that a religious guidance approach can help solve problems of mental health disorders. Unfortunately, they do not understand practical Islamic guidance as an effort to prevent and promote mental health disorders. This study aims to analyse the Islamic religious guidance approach for mental health disorders. This research uses qualitative methods with a literature study approach. The data collection strategy was sourced from seven published Scopus-indexed journal literature in 2018-2023 using the keywords